Getting started in stock investing & trading - Thomsett, Michael C (Hoboken, NJ : Wiley, 2013)
'Takes beginning investors and traders through the essential information they need to know before they decide what kind of participant to be in the equities market. The book explains the risks, benefits, features, and definitions of both investing and trading. The sequence of chapters in parts I and II of the book are similar in the sense that they address the same topics but for different audiences (investors versus traders)'--
Includes bibliographical references (p. 289) and index.
Keywords: Stocks -- United States; Investments -- United States